(untitled) (Global Journal of Human-Social Science, 2015)
Introduction-In this paper, the researcher comprehensively examines the cultivation theory. Conceptualized by George Gerbner in the 1960s and 1970s, the theory has been questioned with every media technological development. In the last six decades, the mass communication field witnessed the propagation of cable, satellite, video games and most recently social media. So far, the theory seems to have survived by continuous adjustment and refinement. Since 2000, over 125 studies have endorsed the theory, which points out to its ability to adapt to a constantly changing media environment. This research discusses the theory since its inception, its growth and expansion, and the future prospects for it. In the first section of the paper, an overview is given on the premises/founding concepts of the theory. Next is a presentation of the added components to the theory and their development over the last sex decades including: The cultivation analysis, the conceptual dimensions, types and measurement of cultivation, and the occurrence of cultivation across the borders.